Tinjauan Yuridis Undang-Undang Perlindungan Data Pribadi Tahun 2022 dalam Menangani Kebocoran Data Pelanggan E-Commerce - Lingga Syailendra Arief; Ruli Purwanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
In the rapidly evolving digital era, data breaches have emerged as a serious threat, particularly in the e-commerce sector which handles vast amounts of customers’ personal data. The protection of personal data has therefore become a crucial issue, requiring effective regulation to ensure digital privacy. In response to this growing concern, Indonesia enacted the Personal Data Protection Law (UU PDP) in 2022 as a significant step toward strengthening digital privacy and security. This study aims to evaluate the effectiveness of the 2022 PDP Law in addressing customer data breach incidents on e-commerce platforms in Indonesia. Using a qualitative approach and case study method, this research analyzes several high-profile data breach cases involving major e-commerce companies in the country. The findings indicate that, although the PDP Law has established a clear legal framework regarding the obligations of reporting and managing data breaches, its implementation still faces multiple challenges. Some companies have not fully complied with the legal timeframes for notifying users, and there is a general lack of transparency in how data breach incidents are managed. These shortcomings reveal a gap between the regulatory framework and practical enforcement in the field. Furthermore, the study highlights the limited public awareness and the insufficient preparedness of some companies in responding to data security incidents in accordance with the law. As a result, the rights of consumers to be informed and protected are not always upheld effectively. This research recommends stronger supervision by relevant authorities to ensure stricter enforcement of the PDP Law. It also underscores the need for ongoing education and intensive training for e-commerce companies to enhance their capacity to prevent, detect, and respond to data breaches in compliance with the legal standards. By reinforcing regulatory implementation and organizational readiness, Indonesia can better safeguard digital consumer rights in the growing e-commerce landscape.